2013
DOI: 10.1111/jrh.12044
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cervical Cancer Screening in the United States‐Mexico Border Region

Abstract: Purpose Hispanic women living on the US-México border experience health disparities, are less likely to access cervical cancer screening services, and have a higher rate of cervical cancer incidence compared to women living in non-border areas. Here we investigate the effects of an intervention delivered by community health workers (CHWs, known as lay health educators or Promotores de Salud in Spanish) on rates of cervical cancer screening in Hispanic women who were out of compliance with recommended screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…The capacity building equipped them with behavior change strategies as evidenced by the significant pre-and post-training changes in perceived skills to promote behavior change and motivate women to be screened (21). This supports our work and others' that CHWs can be actively involved in behavior change if provided with appropriate training and supervision (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 76%
“…The capacity building equipped them with behavior change strategies as evidenced by the significant pre-and post-training changes in perceived skills to promote behavior change and motivate women to be screened (21). This supports our work and others' that CHWs can be actively involved in behavior change if provided with appropriate training and supervision (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 76%
“…Promoteres de salud have increased cervical cancer screening in Hispanic women in the United States-Mexico border region [18], which suggests this could be an effective method to increase HPV vaccination among similar vulnerable populations. Further, there is a need to encourage outreach to the LBGTQ community to address unique issues and challenges regarding access to care and vaccinations for this population.…”
Section: Resultsmentioning
confidence: 99%
“…Since Hispanics/Latinos represent the largest ethnic minority group in the U.S., efforts to improve cervical cancer prevention among this population will have a significant public health impact on incidence and mortality rates [28]. There exists variability in cervical cancer incidence and mortality rates among Hispanic/Latino subgroups, with higher rates as well as greater barriers to screening among newer immigrant Hispanic/Latina women in the Midwest, Southeast, and those living near the United States-Mexico border region, all of whom are primarily of Mexican origin [36, 32, 21]. Research has shown that some Hispanic/Latino groups such as Puerto Ricans and Cubans have higher screening rates than Mexican Americans [1].…”
Section: Introductionmentioning
confidence: 99%